The effect of joint orientation on passive movement of the dog’s stifle - Yair, Nadav; Yiapanis, Christos; Ben-Amotz, Ron; Milgram, Joshua (Frontiers in Veterinary Science, 2023)
Passive motion in an unloaded stifle and a 3D model of the same stifle have been used to identify isometric points at the origin and insertion of the cranial cruciate ligament (CCL) in the dog. Effect of cutting the CCL on passive motion of the stifle in different orientations, is unknown. The aim of this study was to describe passive movement of the tibia relative to the femur in dogs, with the stifle in three positions, and with the CCL intact and cut. Ten cadaveric hind limbs were obtained from dogs weighing between 20kg and 25kg and prepared for testing in a custom-built joint testing machine. The stifle was tested in three different positions with data collected, using an electromagnetic tracking system, with the stifle in full extension (0°) and at 20°, 30°, 40°, 45°, and 55° of stifle flexion/extension. Data was gathered at each angle during 2 cycles of flexion and extension with the CCL intact and cut. Flexion of the stifle resulted in caudal translation and internal rotation of the tibia relative to the femur, with cranial translation and external rotation occurring during extension along the identical path. Cutting the cranial cruciate ligament did not result in significant differences in translation or rotation when the stifle was orientated in a position which approximated the standing position of a dog. Isometric points at the origin and insertion of the CCL can potentially be identified in CCL deficient stifles using a technique based on passive motion of an intact stifle.